Psychosocial interventions and the demoralisation of humanitarianism - Pupavac, Vanessa (Cambridge University Press, 2004)
Summary: This paper critically analyses from a political sociology standpoint the international conceptualization of war-affected populations as traumatized and in need of therapeutic interventions. It argues for the importance of looking beyond the epidemiological literature to understand trauma responses globally. The paper explores how the imperative for international psychosocial programmes lies in developments within donor countries and debates in their humanitarian sectors over the efficacy of traditional aid responses. The aim of the paper is threefold. First, it discusses the emotional norms of donor states, highlighting the psychologising of social issues and the cultural expectations of individual vulnerability. Second it examines the demoralization of humanitarianism in the 1990s and how this facilitated the rise of international psychosocial work and the psychologising of war. Third, it draws attention to the limitations of a mental health model in Croatia, a country which has been receptive to international psychosocial programmes. Finally it concludes that the prevalent trauma approaches may inhibit recovery and argues for the need to re-moralize resilience. Please note this is not a final proofed version. A final proofed version of this paper was published under the following reference: Vanessa Pupavac (2004) ‘Psychosocial Interventions and the Demoralisation of Humanitarianism.’ Journal of Biosocial Science, Vol. 36 pp. 491-504. Special issue on Mental Well-being in Complex Emergencies edited by Astier Almedom at Tufts University.